Effects of ELF-PEMF exposure on spontaneous alternation, anxiety, motor co-ordination and locomotor activity of adult wistar rats and viability of C6 (Glial) cells in culture. (February 2023) - Tekam, Chandra Kant Singh; Majumdar, Shreyasi; Kumari, Pooja; Prajapati, Santosh Kumar; Sahi, Ajay Kumar; Shinde, Saksha; Singh, Richa; Samaiya, Puneet Kumar; Patnaik, Ranjana; Krishnamurthy, Sairam; Mahto, Sanjeev Kumar
Abstract: The effects of ELF-PEMF exposure on spontaneous alternation, anxiety, motor coordination, and locomotor activity have been discussed in various pre-clinical and clinical settings. Several epidemiological and experimental studies have demonstrated the potential effects of ELF-PEMF when exposed > ∼1 h/day; however, very few studies have focused on understanding the influence of ELF-PEMF exposure of 1–3 mT with an exposure duration of < 1 h/day on spontaneous alternation, anxiety, motor coordination, and locomotor activity. Hence, we attempted to study the effects of ELF-PEMF exposure of 1–3 mT, 50 Hz with an exposure duration of 20 min each with a 4 h gap (2 times) on the cellular proliferation and morphologies of C6 (Glial) cells and spontaneous alternation, anxiety, motor coordination and locomotor activity of Wistar rats under in vitro and in vivo conditions, respectively. The results showed that ELF-PEMF exposure did not induce any significant levels of cellular fragmentation and changes in the morphology of glial cells. Also, the outcomes revealed no noticeable effects on spontaneous alternation, anxiety, motor coordination, and locomotor activity in PEMF-exposed groups compared with the control. No undesirable side effects were observed at the highest dose (B=3 mT). We also performed histological analysis of the selected brain sections (hippocampus and cortex) following ELF-PEMF exposure. Incidentally, no significant changes were observed in cortical cell counts, tissue structure, and morphology. Graphical Abstract: ga1